2005
DOI: 10.1063/1.2033624
|View full text |Cite
|
Sign up to set email alerts
|

Optimal rotary control of the cylinder wake using proper orthogonal decomposition reduced-order model

Abstract: In this paper we investigate the optimal control approach for the active control and drag optimization of incompressible viscous flow past circular cylinders. The control function is the time angular velocity of the rotating cylinder. The wake flow is solved in the laminar regime (Re = 200) with a finite element method. Due to the CPU and memory costs related to the optimal control theory, a Proper Orthogonal Decomposition (POD) Reduced Order Model (ROM) is used as the state equation. The key enablers to an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
227
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(243 citation statements)
references
References 41 publications
11
227
1
4
Order By: Relevance
“…Following this approach the POD functions are determined once for all at the beginning of the optimization process and no refresh is realized. This method was successfully applied to control the cylinder wake flow in [15]. It was demonstrated that an accurate and robust POD ROM can be derived using a snapshot ensemble for POD based on chirp-forced transients of the flow.…”
Section: A Generic Configuration Of Separated Flows: the Cylinder Wakmentioning
confidence: 99%
See 3 more Smart Citations
“…Following this approach the POD functions are determined once for all at the beginning of the optimization process and no refresh is realized. This method was successfully applied to control the cylinder wake flow in [15]. It was demonstrated that an accurate and robust POD ROM can be derived using a snapshot ensemble for POD based on chirp-forced transients of the flow.…”
Section: A Generic Configuration Of Separated Flows: the Cylinder Wakmentioning
confidence: 99%
“…Since the POD basis is intrinsic to a particular flow, we need to give special attention to adapt the POD ROM (and the POD basis naturally) to changes in physics when the flow is altered by control. This central question is discussed in more details in [15] where two strategies are evidenced for use of POD ROM in an optimization setting. A first approach consists in distributing uniformly in the control parameter space the snapshot ensemble to be used for POD.…”
Section: Reduced-order Models In Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…On least-order flow representations for aerodynamics and aeroacoustics 371 force-related structures (Protas & Wesfreid 2003;Bergmann, Cordier & Brancher 2005), this constitutes an exercise of a first check of OID's physical plausibility. A major goal of the modelling efforts of this paper is to provide a physical understanding of shear flow noise generation.…”
Section: Downloadedmentioning
confidence: 99%